Frequency-domain Analysis Of Resonant Current Controllers For Active Power Filters - Rodrigues Limongi, Leonardo; Roiu, Daniel; Bojoi, Radu; Tenconi, Alberto (Eletrônica de Potência, 2010)
This paper performs a frequency-domain analysis of three different resonant current controllers for active power filters. Respect to previous papers, the novelty consists of a stability analysis of the closed loop system using the Nyquist criterion. To perform this analysis, the time delay introduced by the inverter and the sampling due to the digital control are taken into account in the current controller closed loop transfer function. This procedure demonstrates the importance and effectiveness of the delay compensation to maintain the whole system stability. Experimental results are presented for a 25 kVA shunt active power filter prototype to confirm the theoretical analysis.